Enhance Argumentative Competence in Natural Science Through a Pedagogical Strategy (Docentes 2.0 Journal, 2021)
The argumentative competencies are part of the competencies considered relevant in education. One of the eight essential competencies proposed by the European Commission is learning to learn, that is, that students are aware of how they know and how to learn. The main objective of this research was to demonstrate the argumentative competence of seventh-grade students in natural sciences through a pedagogical strategy designed as a Moodle tool in an institution in Bogotá (Colombia). The approach used is mixed (quantitative-qualitative). The study sample is intentional, with 25 participants, between the ages of 12 and 13 of both genders, male and female, with heterogeneous socioeconomic stratum 2 and 3. The instrument used was a survey as a data collection tool. It was allowed to recognize some competencies in students with skills, knowledge, and attitudes towards natural sciences. The research entitled to conclude that the students realized the importance of working with Information and Communication Technologies (ICT) since it allows them to be more autonomous in their work at school, keeping them more active in the argumentation process in natural sciences, identifying the rely on technology to enhance those skills in which they have some degree of difficulty for them.
Keywords: Argumentative competence; strategy; pedagogy